AN EXPERT SYSTEM TO DISTINGUISH DRUG ADDICTS USING ID3 ALGORITHM - Sravani, S V N S; Laxminarayanamma, K; Reddy, K Srinivasa; Reddy, K Srinivasa (International Journal of Psychosocial Rehabilitation, 2020)
The key enabler of all the diseases is drug addiction. The individual who uses drugs is dependent upon different ailments. Only few people refuse to take drugs, while many of the teens are curious about using drugs. The reason is to build up a specialist framework (Expert system) that can anticipate whether the individual is dependent on drugs or not. In Artificial intelligence, an expert system is a specialist in logic, development and management, capable of advising, instructing man in the prize of the decision, of the demonstration, of the explanation, of the results and of the conclusion. It uses reasoning procedures to solve difficult problems by using a set of complex mathematical equations. Expert systems are understandable and highly sensitive. The Expert system is utilized in numerous fields, for example, finance, agriculture, education, computer design, and so on., but medicine is the most mainstream field that assists specialists with forestalling and fix of powerless sicknesses early, for example, heart diseases, skin cancer, lung disease, diabetes and some more. Here an Expert system is created utilizing the decision tree algorithm ID3, which is a psychological test that contains in excess of 65,000 guidelines, which separates the low, moderate and extreme condition of the client dependent on the test in which to react.